Miss Julia weathers the storm [large type] - Ross, Ann B. (Ross, Ann B. Miss Julia series., 2017)
"Miss Julia's sweet and generous husband, Sam, has decided to take a big group trip to the beach, inviting family and friends. While Miss Julia prepares for the big trip, her longtime friend LuAnne comes to her with a horrifying discovery-- her husband may be cheating on her. Julia invites LuAnne along to the beach to get away and clear her head-- and to keep from doing anything rash. Everyone settles into the rental house and six-year-old Latisha, their beloved housekeeper Lillian's great-grandaughter, is having a blast searching for seashells when she discovers some much more valuable treasures that have washed up from a strong storm off the coast. As the storm nears, the crew packs up to head back to Abbotsville, and it appears that the three strangers they met on the beach-- who seemed a bit too interested in little Latisha's treasures-- have followed them back to their sleepy town."--Amazon.com